Kajian Strategi Pemasaran Dan Pengembangan Produk Buket Bunga Sebagai Implementasi Progam MBKM: Studi Kasus Posie Florist - Faturrohman Firdaus; Handy Nugraha; Santi Putriani (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the marketing strategies and product development of Posie Florist, a business engaged in the creative economy sector specializing in flower bouquets. Using a qualitative approach through observation and interviews, the findings reveal that current marketing efforts are suboptimal, particularly in digital media utilization and market segmentation. The products offered tend to be monotonous with little differentiation, making it difficult to compete and build customer loyalty. A narrow focus on the student market further limits the business's expansion potential. The study recommends product diversification, brand identity reinforcement, and the use of social media and strategic collaborations to enhance competitiveness. The findings are expected to serve as practical insights for developing florist businesses within Indonesia’s growing creative economy